Synthesis of hydroxylated polyisoprene-graft-polylactide copolymer - Neoh, Benjamin Di-Shen; Siti Fairus Mohd Yusoff,; Akiyoshi, Takeno; Shinya, Takahashi; Farah Hannan Anuar, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Polyisoprene (PI) has been widely used in many industries for decades. Many researches have reported that most significant weaknesses of polyisoprene are caused by unsaturated double bond C=C. The aim of this research was to synthesis and characterize a new copolymer utilizing the unsaturated double bond C=C of polyisoprene. PI is first modified to form hydroxylated polyisoprene (PIOH). The absence of alkene proton peak in NMR spectrum of PIOH is a strong evidence that the unsaturation of PI has been reduced. After that, PIOH is subjected as an initiator for the ringopening polymerization of D,L-lactide in bulk condition to form hydroxylated polyisoprene-graft-polylactide copolymer (PI-g-PLA). The NMR spectrum of the new copolymer structure showed an unique peak at 4.09 ppm corresponding to methine proton of polyisoprene backbone adjacent to the PLA chains, indicating the grafting of D,L-lactide is successful to form PIOH-g-PLA. The average molecular weight, Mw of PIOH-g-PLA was significantly increased compared to PIOH, from 38260 to 56870 according to GPC. The surface of PIOH-g-PLA displayed significantly higher wettability and hidrophilicity than polyisoprene with water contact angle of below 30°. This owes to the terminal hydroxyl groups of PLA chains that lead to the formation of hydrogen bonds. Thermal stability studies by TGA and DTG of PIOH-g-PLA indicated two thermal degradations at Tmax 260 and 392 ℃ corresponding to PLA side chains and PIOH backbone, respectively, with PIOH exhibiting highest thermal stability compared to PI and the graft copolymer.